The current crisis in the NHS: are we missing the point? An essay by Jan Filochowski. (24th April 2015) - Filochowski, Jan
Abstract : Jan Filochowski argues that the NHS can no longer respond to financial challenges by simply reducing capacity and has to adopt a new approach that acknowledges and meets demand